SinA( 1+ tan A ) + cos A ( 1 + cot A ) = sec A + cosec A
Answers
Answered by
5
Sin A ( 1 + tan A) + cos A ( 1 + cot A) = Sec A + cosec A
Solving the LHS
Solving the brackets
→ Sin A + Sin A tan A + cos A + cos A cot A
Now , we know that
- Tan A = Sin A/ Cos A
- Cot A = Cos A / sin A
•°• Sin A + (Sin A tan A) + cos A + (cos A cot A)
→ Sin A + (Sin A . Sin A/ cos A) + cos A +( cos A. cos A/ sin A )
→ Sin A + (sin²A / cos A) + cos A + (cos² A / sin A )
Taking the fractions :
Separating the terms :
LHS = RHS
Hence proved
Similar questions